De novo, deleterious sequence variants that alter the transcriptional activity of the homeoprotein PBX1 are associated with intellectual disability and pleiotropic developmental defects. (22nd September 2017) - Slavotinek, Anne; Risolino, Maurizio; Losa, Marta; Cho, Megan T; Monaghan, Kristin G; Schneidman-Duhovny, Dina; Parisotto, Sarah; Herkert, Johanna C; Stegmann, Alexander P A; Miller, Kathryn; Shur, Natasha; Chui, Jacqueline; et al.
Abstract: We present eight patients with de novo, deleterious sequence variants in the PBX1 gene. PBX1 encodes a three amino acid loop extension (TALE) homeodomain transcription factor that forms multimeric complexes with TALE and HOX proteins to regulate target gene transcription during development. As previously reported, Pbx1 homozygous mutant mice ( Pbx1 −/− ) develop malformations and hypoplasia or aplasia of multiple organs, including the craniofacial skeleton, ear, branchial arches, heart, lungs, diaphragm, gut, kidneys, and gonads. Clinical findings similar to those in Pbx mutant mice were observed in all patients with varying expressivity and severity, including external ear anomalies, abnormal branchial arch derivatives, heart malformations, diaphragmatic hernia, renal hypoplasia and ambiguous genitalia. All patients but one had developmental delays. Previously reported patients with congenital anomalies affecting the kidney and urinary tract exhibited deletions and loss of function variants in PBX1 . The sequence variants in our cases included missense substitutions adjacent to the PBX1 homeodomain (p.Arg184Pro, p.Met224Lys, and p.Arg227Pro) or within the homeodomain (p.Arg234Pro, and p.Arg235Gln), whereas p.Ser262Gln fs *2, and p.Arg288* yielded truncated PBX1 proteins. Functional studies on five PBX1 sequence variants revealed perturbation of intrinsic, PBX-dependent transactivation ability and altered nuclear translocation, suggesting abnormal interactions between mutant PBX1 proteins and wild-type TALE or HOX cofactors. It is likely that the mutations directly affect the transcription of PBX1 target genes to impact embryonic development. We conclude that deleterious sequence variants in PBX1 cause intellectual disability and pleiotropic malformations resembling those in Pbx1 mutant mice, arguing for strong conservation of gene function between these two species.